Biomarker and surrogate development in vascularised composite allograft transplantation: Current progress and future challenges. Issue 4 (April 2021) - Honeyman, Calum; Stark, Helen; Wang, Hayson Chenyu; Hester, Joanna; Issa, Fadi; Giele, Henk
Summary: Vascularised composite allograft (VCA) transplantation is now a feasible reconstructive option for patients who have suffered significant soft tissue injuries. However, despite numerous technical advances in the field over two decades, a number of challenges remain, not least the management of transplant rejection. Part of the difficulty faced by clinicians is the early recognition and prevention of acute rejection episodes. Whilst this is potentially easier in VCAs than solid organ transplants, due to their visible skin component, at present the only validated method for the diagnosis of acute rejection is histological examination of a tissue biopsy. The aim of this review article is to provide an evidence-based overview of progress in the field of VCA biomarker discovery, including immune cell subsets, immune cell effector pathways, and circulating markers of allograft damage, and to discuss future challenges in the field.